Digital civility: A study of Muhammadiyah’s information jurisprudence - Anugrah Ainul Yaqin (The Journal of Religion and Communication Studies, 2026)
Background: The digital era has profoundly transformed the way people communicate and process information. However, this advancement has also brought serious challenges, including the erosion of digital civility through hoaxes, hate speech, and ethical degradation in communication. This article aims to examine the relevance of Muhammadiyah’s fiqh al-ma‘lumat (information jurisprudence) as an Islamic ethical framework that responds to the dynamics of contemporary media. Methods: Using a qualitative approach through library research, this study analyzes official Muhammadiyah documents, scholarly works, and supporting literature. Findings: The findings indicate that Muhammadiyah’s information fiqh embodies core ethical principles such as tabayyun (verification), tatsabbut (caution), ta’awun (collaboration), and amar ma’ruf nahi munkar (promoting good and preventing evil), all of which are highly contextual and applicable in today’s digital discourse. Moreover, this fiqh reflects thematic ijtihad that is not only normative, but also educative and transformative. Therefore, Muhammadiyah’s approach plays a strategic role in cultivating a digitally literate Muslim society rooted in ethics, accountability, and religious values. Conclusion: The study concludes that Muhammadiyah’s Fikih Informasi provides a comprehensive and contextually relevant Islamic ethical framework that strengthens digital civility by guiding Muslims to navigate misinformation, unethical communication, and spiritual challenges in the digital era through principles of verification, caution, cooperation, and moral responsibility. Novelty/Originality of this article: This article lies in its articulation of Muhammadiyah’s fiqh al-ma‘lumat as a distinctive Islamic ethical-communication framework that not only addresses contemporary challenges of digital discourse—such as misinformation and ethical erosion—but also aligns with the journal’s scope by offering an original integration of religious rhetoric, digital media practices, and transformative religious communication for shaping digitally responsible Muslim communities.